富山市山岳域の地質学的，地形学的特徴と植生−Ⅱ - 藤田 将人; 増渕 佳子; 太田 道人 (富山市科学博物館, 2015)
常願寺川源流域及び黒部川源流域の特徴的な地形や地質，生物分布等に関する知見を得ることを目的とし，黒部川上流域（太郎山～北ノ俣岳～黒部五郎岳～三俣蓮華岳〜新穂高）までの登山道周辺）の予察調査を行った．調査地の地質は，主にジュラ紀の花崗岩類，後期ジュラ紀～前期白亜紀の堆積岩類（手取層群），前期白亜紀の閃緑岩からなる．調査地域内の氷河地形として，黒部五郎カールとそのカール内の羊背岩を確認した．調査地の植生は，日本海からの冬期季節風に対して文字通り第一線に位置する地域であることから，植生の大要は，冬期季節風の風上側に当たる西向き斜面の稜線付近には雪が積もらず，一方の東向き斜面は吹きだまりとなることを基本とする，強風との関係性で捉えられる．相観により植物群落を区分し，風衝地植物群落，ハイマツ群落，雪田草原，亜高山帯針葉樹林，亜高山帯湿性草原，亜高山帯広葉樹林，高等植物を欠く岩礫地などの存在を確認し，これらを強風との関係性に注目して記録した． We have researched the geology, topography and vegetations of the alpine and subalpine zone between Taroyama and Mitsumataregedake in Toyama City. The geology is mainly composed of Jurassic granitic rocks, Upper Jurassic to Lower Cretaceous sedimentary rocks (Tetori Group), and Early Cretaceous diorite. Glacial cirques and glaciated knobs are developed in the east side slope of Kurobegorodake. Plant fossils were found from the siltstone of the Tetori Group at the ridge between Taroyama and Kitanomatadake. Remarkable vegetations affected by strong wind were observed on the west slopes of Kitanomatadake. Vegetations in the Kurobegorodake cirque were described. Sibbaldia procumbens which were thought to grow on small gravel in the Tateyama mountains were growing on a sandy slope of Yumioridake.